Colonic perforation in a patient with systemic lupus erythematosus accompanied by cytomegalovirus infection: A case report. (2016) - Tachikawa, Yuichi; Nozawa, Hiroaki; Tanaka, Junichiro; Nishikawa, Takeshi; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Hata, Keisuke; Kawai, Kazushige; Kazama, Shinsuke; Yamaguchi, Hironori; Ishihara, Soichiro; Sunami, Eiji; et al.
Highlights: There were only two reported cases of SLE manifesting gastrointestinal perforation. Our case is the first SLE patient who developed fatal perforation in the colon. CMV and microembolism-induced ischemia seemed responsible for the perforation. Abstract: Introduction: Cytomegalovirus (CMV) infection of the gastrointestinal tract is an uncommon illness, but can be observed in immunocompromised patients. Systemic lupus erythematosus (SLE) patients are generally at high risk of CMV infection. Here we report a subacute progressive case of colitis in SLE accompanied by cytomegalovirus infection. Presentation of case: The patient, a 79-year-old woman, was hospitalized complaining of fever, polyarthritis, and skin ulcer that had lasted seven days. She additionally manifested vomiting, high fever, and right abdominal pain within two weeks thereafter, and was diagnosed with perforation of the intestine. Emergency operation was carried out for panperitonitis due to perforation of one of the multiple colon ulcers. Multidisciplinary postoperative treatment could not save her life. Pathological examination suggested that cytomegalovirus infection as well as cholesterin embolization contributed to the rapid progression of colitis. Discussion: There have been only a limited number of case reports of CMV enteritis in SLE. Moreover, only two SLE patients on multiple medications have been reported to experience gastrointestinal perforation. Viral infections, including CMV, can induce clinical manifestations resembling SLE and for this reason we suspect that there are potentially many more patients misdiagnosed and/or unreported. Conclusion: Our case underscores the importance of exploring the possibility of CMV infection as a differential diagnosis in SLE patients with obvious gastrointestinal symptoms who were treated by immunosuppressive drugs.